2016
DOI: 10.5539/gjhs.v9n5p10
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Probabilities of HBV markers among Health Care Workers in Public Hospitals in White Nile State, Sudan; 2013

Abstract: Background: Health-care workers are having highest probability of being infected with HBV.Objective: To determine conditional probability of sero-prevalence of hepatitis B virus markers among health care workers in White Nile State, Sudan. Methods:A cross sectional study design with analytical approach was used. Three hundred eighty five health care workers were selected randomly. An interview was carried using a pre-tested questionnaire and five ml venous blood samples were consented. Blood samples were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…A total of 43 articles were found from member countries of EMRO and Middle East that reported the prevalence of HBsAg in HCWs, and included a sample of 110179 people. Of these articles, 17 had been conducted in Iran,[1734353637383940414243444546474849] 3 in Iraq,[505152] 2 in Libya,[5354] 2 in Morocco,[1655] 4 in Pakistan,[15565758] 1 in Palestine,[59] 1 in Saudi Arabia,[60] 4 in Sudan,[14616263] 8 in Turkey,[6465666768697071] and 1 in Yemen. [72]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 43 articles were found from member countries of EMRO and Middle East that reported the prevalence of HBsAg in HCWs, and included a sample of 110179 people. Of these articles, 17 had been conducted in Iran,[1734353637383940414243444546474849] 3 in Iraq,[505152] 2 in Libya,[5354] 2 in Morocco,[1655] 4 in Pakistan,[15565758] 1 in Palestine,[59] 1 in Saudi Arabia,[60] 4 in Sudan,[14616263] 8 in Turkey,[6465666768697071] and 1 in Yemen. [72]…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted in Sudan, the prevalence of HBsAg in HCWs was reported 16%. [14] The spread of HBV in HCWs in these regions is such that the prevalence of HBsAg has been reported 4.7% in Pakistan,[15] 1% in Morocco,[16] and 0.2% in Iran. [17] Understanding the prevalence of some infections such as HBsAg may provide useful information for health policymakers to consider the best preventive measures for HCWs in different societies.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with studies done in Nigeria that showed high rates of HBsAg among illiterate, unmarried pregnant women attending ante natal care, and among HCWs in White Nile State, Sudan. [22,25]. Regarding duration of work and the probability for the village midwife to be a carrier (positive HBsAg) given that she is infected (positive Anti-HBcore), the maximum score was reported among those who worked for 1-2 years, followed by 10-20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Among health care providers in White Nile State, Sudan, there is a high prevalence and conditional probabilities of HBV markers. There is statistical association between carrier and highly infectivity rate of HBV and departments of Obstetrics & gynaecology, surgery, Laboratory technicians and HCWs with working duration up to 5 years [22,23] …”
Section: Background Informationmentioning
confidence: 99%